Effects of different scanning parameters of cone beam CT on displaying microstructure of mandible - DONG Qi, FENG Yongjing, GAO Antian, LIN Zitong (口腔疾病防治)
Objective To compare the effect of different scanning parameters of cone beam computed tomography (CBCT) on displaying trabecular microstructure in the anterior region of the mental foramen of the mandible, and to provide a basis for the rational selection of CBCT scanning parameters. Methods This study was approved by the Ethics Committee of the Affiliated Stomatological Hospital, Medical School of Nanjing University. An in vitro study was conducted using CBCT (ProMax 3D Mid) to scan eight dry human mandibular specimens with five scanning protocols: Group A: 90 kV/6.3 mA, Group B: 90 kV/8.0 mA, Group C: 90 kV/10.0 mA, Group D: 75 kV/8.0 mA, and Group E: 60 kV/8.0 mA, resulting in a total of 40 CBCT images. Entrance surface dose (ESD) and computed tomography dose index (CTDI) under different scanning conditions were recorded. The original CBCT images were imported into the image analysis software (Hiscan Analyzer) to measure four trabecular bone microstructural parameters in the region of interest of the mandible: trabecular thickness (Tb.Th), trabecular number (Tb.N), trabecular space (Tb.Sp), and bone volume/tissue volume (BV/TV). A total of 108 CBCT images were retrospectively collected from clinical implant patients using any of the 90 kV/6.3 mA, 90 kV/8.0 mA, or 90 kV/10.0 mA scanning conditions, and the above four parameters of the region of interest of the mandible were also measured. SPSS 26.0 software was used to compare the differences in the four trabecular bone microstructural parameters between the CBCT images of the mandibular specimens in vitro and clinical patients in vivo. Results The in vitro study results showed that reducing the tube voltage and tube current would lead to a decrease in the ESD and CTDI. When the tube voltage was maintained at 90 kV and the tube current was changed, BV/TV, Tb.N, and Tb.Th values increased with the increase of tube current; Tb.Sp values decreased with the increase of tube current, but there was no statistically significant difference in the four bone morphological parameters (P > 0.05). When the tube current was maintained at 8.0 mA and the tube voltage was altered, BV/TV and Tb.N decreased with the increase of tube voltage, Tb.Sp values increased with the increase of tube voltage, and BV/TV, Tb.N, and Tb.Sp showed statistically significant differences (P < 0.05). In clinical patients undergoing CBCT scanning, when the tube voltage was 90 kV and the tube current was different (6.3, 8.0, 10.0 mA), there was no statistically significant difference in the four bone morphological parameters (P > 0.05). Conclusions In this study, when the tube voltage was fixed at 90 kV, there was no difference in the trabecular microstructure of the anterior region of the mandible when the tube current was increased. When CBCT scanning of clinical patients needs to show the trabecular microstructure of the anterior region of the mandible, the tube current can be appropriately reduced to decrease the radiation dose received by the patient. Thus, it is recommended to use the parameters 90 kV and 6.3 mA for CBCT scanning.